THE EFFECT OF POLYELECTROLYTES ON CALCIUM OXALATE CRYSTALLIZATION - Akyol, Emel; Oner, Mualla (YILDIZ TECHNICAL UNIV, 2007)
In this study, the effects of polyelectrolytes on the growth mechanism of the calcium oxalate monohydrate (COM) crystals, which have great importance both in industry and biomineralization have been investigated. The crystal growth experiments were carried out in aqueous solutions at 37 degrees C by the constant composition method. Polyacrylic acid and poly (ethylene glycol-block-acrylic acid) copolymer were used as additives. The results of the experiment show that the inhibition of crystallization rate depends on the nature of the polymer and its concentration. Polyelectrolyte effects were interpreted in terms of the adsorption of inhibitors onto the active growth sites on the crystal surface.
Keywords: Calcium oxalate monohydrate (COM); crystallization; biomineralization; polyelectrolytes; constant composition method; Engineering